A qualitative study on parents' concerns about adult children with intellectual disabilities amid the COVID‐19 pandemic in South Korea. Issue 4 (10th March 2021) - Kim, Min Ah; Yi, Jaehee; Jung, Sang Mi; Hwang, Shinyeong; Sung, Jimin
Abstract: Background: This study aimed to understand parents' concerns about their adult child with intellectual disabilities due to the restriction of community‐based services amid the COVID‐19 pandemic in South Korea. Methods: In‐depth interviews were conducted face‐to‐face or by telephone with 19 parents of adult children with intellectual disabilities who had to stop using community‐based services. Results: Participants worried that their adult child was not aware of the seriousness of COVID‐19, was more susceptible to the COVID‐19 virus, could not recognize self‐infection and could have fatal consequences of getting infected with COVID‐19. They expected challenges in their adult child's life (losing a daily routine, being isolated, regression in skills, becoming bored, lacking physical activities and increased behavioural challenges) but also experienced adjustments and hopes. Conclusion: The study demonstrated parents' worry about their adult child becoming infected with COVID‐19, highlighting the urgent need for community‐based services to address psychosocial challenges during the pandemic.